DIETARY INTAKE OF IRON AND CALCIUM FOR ADOLESCENTS ON REPRODUCTIVE PHASE OF A PUBLIC SCHOOL OF PETROLINA - PERNAMBUCO - FERREIRA, DARLING SILVA DOS SANTOS; TORRES, MARINA AMARAL ALMEIDA; SILVA, INGRID RAFAELLA MAURICIO; Omena Messias, Cristhiane Maria Bazílio de (Journal of Health Care, 2015)
Objective: To estimate the dietary intake of iron and calcium by adolescents in the reproductive phase in apublic school of Petrolina, Pernambuco. Methods: 274 female adolescents, aged between 11 and 17 yearsold, were interviewed. The dietary intake survey was conducted through 24-hour recall (R24h). To calculateiron and calcium intake in the adolescent population, we used as reference the Dietary Reference intakes/Reference Daily Intake - Recommended Dietary Allowances/Dietary Intake Recommended and AdequateIntake/Intake and Adequate. The data were described as means and standard deviations, verifying therelation between the variables: age and nutrient intake. We used the softwares Excel (2013 Version) andGraph Prism (6.01 Version) for statistical treatment of the data. Results: We could verify that the averageiron intake was higher than the recommended in 81 (29.54%) adolescents, while 193 (70.04%) didnot achieve the recommended amount. Regarding the calcium intake, only 47 (17.15%) demonstratedadequate intake. Among the iron-rich plant-based foods, the consumption of beans (83.2%) stood out.Meat (61.31%) and eggs (19.7%) were the foods of animal origin consumed the most. The food sources ofcalcium with the highest intakes were: whole milk (63.1%), cheese (43.8%), yogurt (27.74%), ice cream(14.6%) and cottage cheese (5.1%), respectively. Conclusions: This study found insufficient intake ofmicronutrients evaluated in most adolescents, highlighting the need for an intervention in order to repairthis deficiency.
Keywords: Adolescence; reproductive phase; food intake; iron and calcium.